3x2+13=61

Simple and best practice solution for 3x2+13=61 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x2+13=61 equation:



3x^2+13=61
We move all terms to the left:
3x^2+13-(61)=0
We add all the numbers together, and all the variables
3x^2-48=0
a = 3; b = 0; c = -48;
Δ = b2-4ac
Δ = 02-4·3·(-48)
Δ = 576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{576}=24$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-24}{2*3}=\frac{-24}{6} =-4 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+24}{2*3}=\frac{24}{6} =4 $

See similar equations:

| 207-y=7 | | 15+7x-2x=20 | | 3c–1=–10 | | 24=24-3(2a-15)-a | | -1.42x=-26.98 | | 4-3x+2x=x | | x−9)2=25 | | (6x-15)=(2x+18)=(2x-13)=180 | | 11x-3=4x+29 | | 8+x+11=180 | | x+(-18)=-7 | | 3x-6-2x=9 | | (2x−13)+(4x−5)=90 | | 7x-4=5x-1.5=x+9 | | 2x-5•0=20 | | -x-19=21+3x | | -10=+3w | | 18-2g=6 | | x-2(5x+2)=9-9x | | 5x²=9x-2=0 | | p/7-8=2 | | a-17=1,825026 | | -5f-30=-60 | | 4x+6=13-5x | | u/8+10.3=-2.5 | | 2x+20=-12 | | 0.5x=0.39 | | -1=7+x | | 4x+6=13−5x | | -1(3c-9)= | | t/3+8=98 | | 2z+7.8=-25.12 |

Equations solver categories